EFFECT OF LOCAL MICROORGANISMS (MOL) OF MORINGA LEAVES ON THE GROWTH AND YIELD OF PAKCOY MUSTARD (Brassical rapa L.) - I Kadek Widya Praptika; I Putu Sujana; I Gusti Ayu Diah Yuniti (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
To support sustainable vegetable cultivation, the use of organic fertilizers is essential for improving soil quality and minimizing pest disturbances. Pak choi is a widely cultivated horticultural crop due to its high nutritional value and strong economic potential, creating a need for more environmentally friendly cultivation practices. One such approach is the use of Local Microorganisms (MOL), produced through the fermentation of natural materials containing active microorganisms from plants or plant parts. These include Rhizobium sp., Azospirillum sp., Azotobacter sp., Pseudomonas sp., Bacillus sp., and phosphate-solubilizing bacteria that support soil fertility and plant growth. Moringa leaves (Moringa oleifera) are a potential source of MOL due to their growth-promoting properties. This study aimed to evaluate the effect of moringa leaf MOL on pak choi growth and to identify the most effective concentration. Conducted at the Bali Agricultural Technology Study Center, the results showed that the treatment had a highly significant effect on plant height, number of leaves, leaf area, total fresh weight, above-ground fresh weight, and total oven-dry weight, but no significant effect on fresh and dry root weight. The highest leaf number was observed at the P3 concentration